Influence of Diabetes-Related Support on Aerobic Activity Among Older African Americans With Type 2 Diabetes. (October 2019) - McCaskill, Gina M.; Bowen, Pamela G.; Lee, Loretta T.; Burgio, Kathryn L.; Leeper, James; Clay, Olivio J.
The objective of this study was to examine the influence of diabetes-related support in promoting aerobic activity in a sample of older African Americans. A secondary data analysis was conducted based on a diabetes self-management study of community-dwelling older African Americans. Logistic regression was conducted to examine the influence of diabetes-related support on aerobic activity. The final model demonstrated that there was a strong relationship between having diabetes-related support and aerobic activity, odds ratio =6.56, 95% confidence interval [2.14, 20.11]. The final model also demonstrated a significant influence based on the total number of chronic health conditions on aerobic activity, odds ratio = 0.63, 95% confidence interval [0.498, 0.802]. Findings suggest that older African Americans with Type 2 diabetes and other chronic health conditions may engage in physical activity if they have diabetes-related support from their family and friends.